IMPROVING STUDENTS’ READING COMPREHENSION THROUGH THE JIGSAW II LEARNING METHOD AT THE SECOND-GRADE OF MAS NIDA’UL KHAIRAAT POMBEWE - AGUS AGUS; Muhammad Ihsan; Nur Asmawati (English Tadris Department, Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) Datokarama Palu, 2021)
This research aimes to investigate the significant effect of applying the jigsaw II learning method at the second-grade of MAS Nida’ul Khairaat Pombewe. The research employed quasi and need pre-test and post-test. The population of this research was all students of the second grade of MAS Nida’ul Khairaat Pombewe. The sample was selected by using quota sampling technique. The samples were 20 students of IPS class as the controlled class and Agama class as the experimental class. The researcher analyzed the data statistically. The mean score of the experimental class was (67.05), it was higher than the mean score of the control class (45). The result of t-counted (2.327) which was higher than the t-table (2.153). The researcher used the 0.05 level of significance and the degree of freedom (df= 10 + 10 – 2). This research has two hypotheses, which were : there is no improvement of the students’ reading comprehension through the Jigsaw II learning method at the second grade of MAS Nida’ul Khairaat Pombewe and : there is improvement of the students’ reading comprehension through the Jigsaw II learning method at the second grade of MAS Nida’ul Khairaat Pombewe.Based on the resuls of the data above it proven that was accepted and was rejected. In conclusion, the use of the Jigsaw II learning method can improve the students’ reading comprehension at the second grade of MAS Nida’ul Khairaat Pombewe.